2005
DOI: 10.1021/ja035182m
|View full text |Cite
|
Sign up to set email alerts
|

Ferrioxamine B Analogues:  Targeting the FoxA Uptake System in the Pathogenic Yersinia enterocolitica

Abstract: A series of ferrioxamine B analogues that target the bacterium Yersinia enterocolitica were prepared. These iron carriers are composed of three hydroxamate-containing monomeric units. Two identical monomers consist of N-hydroxy-3-aminopropionic acid coupled with beta-alanine, and a third unit at the amino terminal is composed of N-hydroxy-3-aminopropionic acid and one of the following amino acids: beta-alanine (1a), phenylalanine (1b), cyclohexylalanine (1c), or glycine (1d). Thermodynamic results for represen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 51 publications
3
24
0
Order By: Relevance
“…The supernatants were then analyzed using UV-visible absorption spectrophotometry. An excess of free DFoB was added to the supernatant to ensure complete complexation of the unreacted FeNTA and the corresponding Fe(III) concentrations were evaluated from the absorbance measurement at 430 nm (LMCT absorption band of FeDFoB at 430 nm, ε 430 = 2950 M -1 •cm -1 ) 7 .…”
Section: Iron Capture Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…The supernatants were then analyzed using UV-visible absorption spectrophotometry. An excess of free DFoB was added to the supernatant to ensure complete complexation of the unreacted FeNTA and the corresponding Fe(III) concentrations were evaluated from the absorbance measurement at 430 nm (LMCT absorption band of FeDFoB at 430 nm, ε 430 = 2950 M -1 •cm -1 ) 7 .…”
Section: Iron Capture Experimentsmentioning
confidence: 99%
“…However, in our experimental conditions (HEPES buffer at 50 mM), the FeNTA absorption was markedly altered by another more intense absorption at about 210 nm (linked to HEPES) which prevents the accurate determination of the iron content (FigureS4.A). To overcome this problem and analyze FeNTA supernatants, free DFoB was added to the supernatant, which rapidly led to the formation of FeDFoB complex which is characterized by a Ligand-to-Fe(III) charge transfer band (i.e., LMCT) of moderate intensity centered at 430 nm (ε 430 = 2950 M -1 •cm -1 )53 . The color changes from light yellow to orange, confirming the exchange of the ligands and the formation of the FeDFoB complex.…”
mentioning
confidence: 99%
“…petrobactin), but more in-depth studies aimed at understanding the mechanism of action are needed for supporting this hypothesis. The siderophore mimicking property of mimosine peptides could be applied for diagnostic and theragnostic treatment of bacterial infections, 76 while mimosine is structurally similar to that of DFP and could form stable complexes with Gd(III) 77 and other lanthanide metals. 37 Mimosine based peptides are structurally and functionally different from classical antibiotics and their MIC activity should be compared with AMPs rather than antibiotics.…”
Section: Dalton Transactionsmentioning
confidence: 99%
“…Among the tested cargo molecules in this study were the Boc protecting group, cyclohexane, naphthalene, phenylmethylbenzene groups, coumarin and the antibiotic ciprofloxacin. In earlier studies it was demonstrated that the siderophores ferrichrome, ferrioxamine and pyochelin can be used to deliver fluorophores into the cytoplasm of Pseudomonas strains and Yersinia enterocolitica [66][67][68][69][70].…”
Section: Illicit Transport Using Siderophore Conjugatesmentioning
confidence: 99%